Stressful life events, parental verbal aggression and depressive symptoms in Malaysian adolescents: the moderating role of parental warmth - Barra, Sharisse May Mate; Baharudin, Rozumah; Zulkefly, Nor Sheereen; Yahya, Amira Najiha; Madon, Zainal (Universiti Putra Malaysia Press, 2019)
Depressive symptomatology is a serious mental health problem that has been observed among Malaysian adolescents. Hence, we conducted a cross-sectional study to identify the risk and protective factors for adolescent depressive symptoms. Specifically, we hypothesized that stressful life events, parental verbal aggression, and parental warmth are significantly associated with adolescent depressive symptoms. A sample of 1092 adolescents (13-19 years old; 447 boys and 645 girls) was recruited using probability proportional to size cluster sampling from 20 secondary schools in four states across Malaysia. Results of the multivariable logistic regression analysis revealed that stressful life events and maternal verbal aggression had significant main effects on depressive symptoms. In the moderation analyses, paternal warmth alleviated the influence of paternal verbal aggression on depressive symptoms. In contrast, both paternal and maternal warmth exacerbated the depressogenic impact of maternal verbal aggression. Such findings could improve prevention and intervention programs for combatting depressive symptoms in Malaysian adolescents.